51 The Impact of Disability on Performance in the Intercollegiate Membership of the Royal College of Surgeons examination (MRCS). (12th October 2021) - Ellis, R; Scrimgeour, D; Cleland, J; Lee, A; Brennan, P
Abstract: Aim: The number of clinicians with disabilities is increasing, however there is no data on the performance of doctors with registered disabilities in the postgraduate environment. If we are to ensure diversity and equality within the workforce, we must first identify whether attainment differences exist in markers of performance. To address this, we assessed the impact of disabilities on performance in the MRCS. Method: All UK medical graduates who had attempted MRCS Part A ( n = 9, 597) and Part B ( n = 4, 562) between 2007-2017 with linked disability data in the UK Medical Education Database (https://www.ukmed.ac.uk ) were included. Univariate analysis identified associations with MRCS performance and logistic regression models identified independent predictors of success. Results: Candidates with registered disabilities (n = 635) had lower MRCS Part A pass rates (46.3% vs 59.8% (p < 0.001)) but similar Part B pass rates (68.2% vs 70.9% (p = 0.339)). They were nearly twice as likely to fail Part A (odds ratio 0.55 [95% Confidence Interval 0.46-0.64]). When prior academic attainment (A-Levels and medical school performance) was accounted for, there was no statistically significant difference in the likelihood of MRCS success ( p >0.05). Pass rates were similar for candidates with specific learning difficulties and those with other registered disabilities ( p >0.05). Conclusions: This is the first study to assess the impact of disability status and type on performance at a postgraduate medical examination. It appears that candidates with registered disabilities performed less well in formal, written examinations generally. Although our data indicate that current MRCS testing accommodations are fair, enabling performance unrestricted by disability.